BEBERAPA CATATAN TENTANG RUU ANTI PORNOGRAFI DAN PORNOAKSI - Mu’allim, Amir (Islamic University of Indonesia, 2006)
The controversies regarding the legalizing of pornography and pornoaction in Indonesia noawadays. There are pros and cons. But the problem is the substance or the goal of the proposed act about pornography and pornoaction. The act gives new horizon how to minimize the negative effect of pornography toward society. According to the writer that Islam and other religions have committed to build polite and order society. Kata kunci: pornografi, pornoaksi,Islam,dan undang-undang.